THE PATHOGENETIC MECHANISMS OF DEVELOPMENT OF PREECLAMPSIA IN WOMEN WITH METABOLIC SYNDROME - E. B. Perederyaeva; T. B. Pshenichnikova; M. D. Andreeva; A. D. Makatsariya (IRBIS LLC, 2016)
Metabolic syndrome is widespread among women of reproductive age. Metabolic syndrome is associated with at higher risk of developing various obstetric complications including severe pre-eclampsia. The hereditary or acquired forms of thrombophilia, proinflammatory status may play an important role in impaired invasion cytotrophoblast and impaired placental development. Pre-eclampsia is seen as a complication of pregnancy, which is due to impaired invasion cytotrophoblast and impaired placental development.